Positional oximetry to screen for pulmonary arteriovenous malformations in HHT. Issue 11 (4th April 2014) - Carpenter, Susan; Josepovici, Janina; Latino, Giuseppe; Ratjen, Felix
Abstract : Orthodeoxia has been described in patients with hereditary haemorrhagic telangiectasia (HHT) and pulmonary arteriovenous malformations (PAVM), but its usefulness in screening children for PAVMs is unknown. We show here that while oximetry is overall lower in children with significant PAVMs, supine and upright oximetry is of no additional diagnostic value indicating that positional oximetry is not a useful screening test for PAVMs.